Lexique de la gastronomie dans le film À la belle étoile (2023) - Riandita Amalia; Diah Vitri Widayanti (Universitas Negeri Semarang, 2026)
A glossary of gastronomy is a lexicon that deals with 9 gastronomic components or vocabulary that includes information on how the words are used in the context of a sentence, including grammatical categories such as nouns, verbs, adjectives, and so on, as well as examples of the usage of the vocabulary. The data source for this research is the entire movie dialogue, shown from beginning to end. The data for this research consist of vocabulary in movie dialogue referring to the 9 components of gastronomy.